Analysis Digital Marketing Through Social Media In Increase Business Income of the Padang Tualang Kabupaten Langkat - Nurafrina Siregar (Yayasan Multidimensi Kreatif, 2023)
This research aims to determine and analyze the influence of quality product , price and Social Media towards Digital Marketing in increase income public Padang Tualang Village regency step With a total sample of 68 respondents. Data collection techniques were carried out using questionnaires. The analysis used is statistical data analysis using tool help program SPSS ( Statistics Packages forSocial Sciences ) 24.0 for windows namely classical assumption testing, multiple linear regression analysis and hypothesis testing. Temporary level coefficient his determination reach 0.726 Which means that variable independent in study This own influence as big as 72.6% of the dependent variable , while the remaining 27.4% is influenced by other factors that were not examined.